Low‐Density Neutrophils in Systemic Lupus Erythematosus. Issue 10 (26th August 2020) - Tay, Sen Hee; Celhar, Teja; Fairhurst, Anna‐Marie
Abstract : Patients with systemic lupus erythematosus (SLE) display increased numbers of immature neutrophils in the blood, but the exact role of these immature neutrophils is unclear. Neutrophils that sediment within the peripheral blood mononuclear cell fraction after density centrifugation of blood are generally defined as low‐density neutrophils (LDNs). Far beyond antimicrobial functions, LDNs are emerging as decision‐shapers during innate and adaptive immune responses. Traditionally, neutrophils have been viewed as a homogeneous population. However, the various LDN populations identified in SLE to date are heterogeneously composed of mixed populations of activated mature neutrophils and immature neutrophils at various stages of differentiation. Controversy also surrounds the role of LDNs in SLE in terms of whether they are proinflammatory or polymorphonuclear myeloid‐derived suppressor cells. It is clear that LDNs in SLE can secrete increased levels of type I interferon (IFN) and that they contribute to the cycle of inflammation and tissue damage. They readily form neutrophil extracellular traps, exposing modified autoantigens and oxidized mitochondrial DNA, which contribute to autoantibody production and type I IFN signaling, respectively. Importantly, the ability of LDNs in SLE to perform canonical neutrophil functions is polarized, based on mature CD10+ and immature CD10− neutrophils. Although this field is still relatively new, multiomic approaches have advanced our understanding of the diverse origins, phenotype, and function of LDNs in SLE. This review updates the literature on the origin and nature of LDNs, their distinctive features, and their biologic roles in the immunopathogenesis and end‐organ damage in SLE.